Polymorphic cobalt diselenide as extremely stable electrocatalyst in acidic media via a phase-mixing strategy - Zhang, Xiao-Long; Hu, Shao-Jin; Zheng, Ya-Rong; Wu, Rui; Gao, Fei-Yue; Yang, Peng-Peng; Niu, Zhuang-Zhuang; Gu, Chao; Yu, Xingxing; Zheng, Xu-Sheng; Ma, Cheng; Zheng, Xiao; et al. (Nature communications, 2019)
Many platinum group metal-free inorganic catalysts have demonstrated high intrinsic activity for diverse important electrode reactions, but their practical use often suffers from undesirable structural degradation and hence poor stability, especially in acidic media. We report here an alkali-heating synthesis to achieve phase-mixed cobalt diselenide material with nearly homogeneous distribution of cubic and orthorhombic phases. Using water electroreduction as a model reaction, we observe that the phase-mixed cobalt diselenide reaches the current density of 10 milliamperes per square centimeter at overpotential of mere 124 millivolts in acidic electrolyte. The catalyst shows no sign of deactivation after more than 400 h of continuous operation and the polarization curve is well retained after 50,000 potential cycles. Experimental and computational investigations uncover a boosted covalency between Co and Se atoms resulting from the phase mixture, which substantially enhances the lattice robustness and thereby the material stability. The findings provide promising design strategy for long-lived catalysts in acid through crystal phase engineering. Noble-metal-free catalysts often show stability issues in acidic media due to structural degradation. Here authors show that phase-mixed engineering of cobalt diselenide electrocatalysts can enable greater covalency of Co-Se bonds and improve robustness for catalyzing hydrogen evolution in acid.